Surgical Emphysema Following Canalplasty for Aural Exostoses. Issue 8 (September 2017) - Baxter, Michael C.; Keller, Matthew; Shah, Anil; Wise, Sean
Abstract : Objective: To describe the presentation and management of surgical emphysema involving the temporomandibular joint and deep neck following exostoses removal. Patient: A 60-year-old male surfer presented with hearing loss and recurrent infections in the right ear. An examination revealed obstructing bony exostoses in the right external auditory canal. He underwent right canalplasty using a postauricular approach. At 5 weeks after surgery, he presented with right otalgia, swelling of the right face and neck, and complaints of a squeaking noise in the right ear with mandibular excursions. An otomicroscopic examination demonstrated a focal area of prolapsing soft tissue along the anterior bony external auditory canal with mandibular movement. The examination also revealed palpable crepitus of the right face and neck. Computed tomography was obtained of the temporal bones and neck confirming a focal anterior canal wall defect allowing communication between the glenoid fossa and external auditory canal with subcutaneous emphysema tracking around the temporomandibular joint into the masticator, parotid, and parapharyngeal spaces. Intervention: Maxillomandibular fixation for 2 weeks with revision canalplasty using a split tragal cartilage graft. Results: At 6 weeks after revision surgery, the patient reported complete resolution of all symptoms. Repeat imaging demonstrated complete resolution of subcutaneous and deep neck emphysema, and the otomicroscopic examination revealed a fully epithelialized external auditory canal with no further evidence of soft tissue prolapse. Conclusion: Maxillomandibular fixation with autologous cartilage graft is an effective management strategy for complications of canalplasty resulting in exposure of the temporomandibular joint capsule and surgical emphysema. Abstract : Supplemental Digital Content is available in the text